Regulatory function of sigma factors RpoS/RpoN in adaptation and spoilage potential of Shewanella baltica. (August 2021) - Feng, Lifang; Bi, Weiwei; Chen, Shuai; Zhu, Junli; Liu, Xiaoxiang
Abstract: Shewanella baltica is a typical specific spoilage organism causing the deterioration of seafood, but the exact regulation of its adaptive and competitive dominance in diverse environments remains undefined. In this study, the regulatory function of two sigma factors, RpoS and RpoN, in environmental adaptation and spoilage potential were evaluated in S. baltica SB02. Two in-frame deletion mutants, Δ rpoS and Δ rpoN, were constructed to explore the roles in their motility, biofilm formation, stress response and spoilage potential, as well as antibiotics by comparing the phenotypes and transcription with those of wild type (WT) strain. Compared with WT strain, the Δ rpoN showed the slower growth and weaker motility due to loss of flagella, while swimming of the Δ rpoS was increased. Deletion of rpoN significantly decreased biofilm biomass, and production of exopolysaccharide and pellicle, resulting in a thinner biofilm structure, while Δ rpoS formed the looser aggregation in biofilm. Resistance of S. baltica to NaCl, heat, ethanol and three oxidizing disinfectants apparently declined in the two mutants compared to WT strain. The Δ rpoN mutant decreased sensory score, accumulation of trimethylamine, putrescine and TVB-N and protease activity, while a weaker effect was observed in Δ rpoS. The two mutants had significantly higher susceptibility to antibiotics than WT strain, especially Δ rpoN. Deficiency of rpoN and rpoS significantly repressed the activities of two diketopiperazines related to quorum sensing (QS). Furthermore, transcriptome analyses revealed that RpoN was involved in the regulation of the expression of 143 genes, mostly including flagellar assembly, nitrogen and amino acid metabolism, ABC transporters . Transcript changes of seven differentially expressed coding sequences were in agreement with the phenotypes observed in the two mutants. Our findings reveal that RpoN, as a central regulator, controls the fitness and bacterial spoilage in S. baltica, while RpoS is a key regulatory factor of stress response. Characterization of these two sigma regulons in Shewanella has expanded current understanding of a possible co-regulatory mechanism with QS for adaptation and spoilage potential. Highlights: Stress resistance in Shewanella baltica was co-regulated by RpoS and RpoN. RpoN modulated flagella, biofilm formation, spoilage in S. baltica. Regulation of two sigma factors might interlink via diketopiperazines mediated QS. RpoN is a central regulator based on the phenotypic and transcriptomic analysis .